2021
DOI: 10.1007/s00704-020-03464-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of meteorological parameters on radio refractivity, equivalent potential temperature and field strength via Mann-Kendall test

Abstract: Trend analysis of meteorological parameters (temperature, pressure, and relative humidity) as well as calculated refractivity, equivalent potential temperature (EPT) for a pseudo-adiabatic process, and field strength in Calabar, Southern Nigeria has been analyzed using Mann-Kendall trend test and Sen's slope estimator. Data of the meteorological parameters were obtained from the Nigerian Meteorological Agency (NiMet) in Calabar for 14 years (2005 -2018). Results show that the maximum and average temperature, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
(49 reference statements)
2
22
0
Order By: Relevance
“…The global total monthly radiation was collected from 2005-2016, and the average was found for each month and presented for all state capitals of the different regions. From mere observations, it can be concluded that the Northern states evidently have higher values of global solar radiation, which is in agreement with facts as the Northern States are hotter, and the Southern States generally have lower temperature values, mainly because of their closeness to the Atlantic Ocean [6,7,8,9]. After using the total monthly global solar radiation with Eq.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The global total monthly radiation was collected from 2005-2016, and the average was found for each month and presented for all state capitals of the different regions. From mere observations, it can be concluded that the Northern states evidently have higher values of global solar radiation, which is in agreement with facts as the Northern States are hotter, and the Southern States generally have lower temperature values, mainly because of their closeness to the Atlantic Ocean [6,7,8,9]. After using the total monthly global solar radiation with Eq.…”
Section: Resultssupporting
confidence: 82%
“…She is located at a globally competitive position with relatively high sunshine intensity and longer average sunshine hours than other countries with better utilization records. Studies [6,7,8,9] have shown that even in her coastal regions, there still exist a great potential for harnessing and utilizing solar energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More details of the Sen's slope estimator and Mann-Kendall test methods, the reader is referred to Sen (1968) and Kendall (1975). Those methods are highly recommended by the World Meteorological Organization and have been widely applied to assess trend of hydrometeorological time series (Agbo et al, 2021;Da Silva et al, 2015;Nyikadzino et al, 2020;You et al, 2016).…”
Section: Model Performance Metricsmentioning
confidence: 99%